The concepts of arrangement in case fees in civil cases - Sumargi,; Slamet Suhartono,; Yovita Arie Mangesti,; Atik Krustiati, (Technium Social Sciences Journal, 2023)
The principle of paying court costs in civil courts is borne by the losing party. The payment for the court fee is taken from the down payment for the court fee paid by the plaintiff. The judge's decision regarding the imposition of court fees on the losing party is a punitive decision, so it must be carried out by the losing party. According to Abdul Kadir Muhamad, when a decision has been enforced, there is no longer any opportunity to use ordinary legal remedies against the decision. Therefore, the judge's decision which has permanent force (incracht van gewijsde) must be implemented without delay.